2019
DOI: 10.1002/dta.2663
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hormonal contraceptives on urinary steroid profile in relation to serum hormone changes and CYP17A1 polymorphism

Abstract: To detect doping with endogenous steroids, six urinary steroids are longitudinally monitored in the athlete biological passport (ABP). These steroids include testosterone, etiocholanolone, androsterone, 5α‐androstane‐3α,17β‐diol, 5β‐androstane‐3α,17β‐diol, and the testosterone isomer epitestosterone. It is known that the intake of hormonal contraceptives may interfere with the ABP biomarkers. A previous study showed that athletes using hormonal contraceptives (HCs) display lower urinary epitestosterone concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 17 publications
(48 reference statements)
6
20
1
1
Order By: Relevance
“…During the follicular phase, the urinary E concentration was suppressed in all the women in the study (Figure 2a). The suppression of E was almost as profound as seen in women taking hormonal contraceptives 9,23,25 . Hormonal contraceptives are not one of the confounding factors that the laboratories have to analyze and report according to TD2018EAAS 14 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…During the follicular phase, the urinary E concentration was suppressed in all the women in the study (Figure 2a). The suppression of E was almost as profound as seen in women taking hormonal contraceptives 9,23,25 . Hormonal contraceptives are not one of the confounding factors that the laboratories have to analyze and report according to TD2018EAAS 14 .…”
Section: Discussionmentioning
confidence: 97%
“…The reason why urinary E increases in the later phase of the cycle is not known but may be associated with the increase of LH and P in the ovulation and luteal phase, respectively. We have seen that hormonal contraceptives (HC) mediated E changes exhibit strong correlation with the gonadotropins to a much larger extent than the other ABP metabolites, 9 whereas no studies have investigated the correlation between urinary E and the other female hormones P and E2. Here, we aim to study if the concentrations of the urinary steroid metabolites differ between the different biological phases of the menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been performed with COC and emergency (i.e., progestin-only, levonorgestrel) contraceptives in healthy women [ 415 ] or elite athletes [ 416 ]. One of the main results was that E concentrations were significantly lower in COC users vs. non-users, whereas T showed no difference, leading to a higher T/E ratio.…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…We found that LC‐CS enhanced the expression of hormone‐related CYP17A1, CYP19A1, AR and SRD5A2. It has been suggested that CYP17A1 encodes cytochrome p450‐17 and is a key enzyme in the steroid hormone synthesis pathway (Ekström et al., 2019).…”
Section: Discussionmentioning
confidence: 99%